Evaluation of treatment patterns, healthcare resource utilization, and costs among patients receiving treatment for cytomegalovirus following allogeneic hematopoietic cell or solid organ transplantation. (31st December 2022) - Cheng, Wendy Y.; Avery, Robin K.; Thompson-Leduc, Philippe; Cheung, Hoi Ching; Bo, Tien; Duh, Mei Sheng; Hirji, Ishan
Abstract: Aim: Management of cytomegalovirus (CMV) infection/disease in transplant recipients may be complicated by toxicities and resistance to conventional antivirals, adding to the overall healthcare burden. We characterized treatment patterns, healthcare resource utilization (HCRU), and costs to elucidate the healthcare burden associated with CMV therapies post-transplant. Materials and methods: A retrospective, longitudinal cohort study of transplant recipients using data from a US commercial insurance claims database (2013–2017) was conducted. Patients with a claim for post-transplant CMV diagnosis and anti-CMV treatment (ganciclovir, valganciclovir, foscarnet, or cidofovir) were identified (Treated CMV cohort) and compared with patients with neither a claim for CMV diagnosis nor anti-CMV treatment (No CMV cohort) for outcomes including HCRU and associated costs. Allogeneic hematopoietic cell transplantation (HCT) or solid organ transplantation (SOT) recipients were analyzed separately. Anti-CMV treatment patterns were assessed in the Treated CMV cohort. Costs were evaluated among subgroups with myelosuppression or nephrotoxicity. Results: Overall, 412 allogeneic HCT and 899 SOT patients were included in the Treated CMV cohorts, of which 41.7% and 52.5%, respectively, received multiple antiviral courses. Treated CMV cohorts compared with No CMV cohorts had higher mean monthly healthcare visits per patient (allogeneic HCT: 8.83 vs 6.61, SOT: 5.61 vs 4.45) and had an incremental adjusted mean monthly cost per patient differences of $8, 157 (allogeneic HCT, p  < .004) and $2, 182 (SOT, p  < .004). Among Treated CMV cohorts, HCRU and costs increased with additional CMV antiviral treatment courses. Mean monthly costs were higher for patients with than without myelosuppression or nephrotoxicity. Limitations: Results may not be generalizable to patients covered by government insurance or outside the USA. Conclusions: CMV post-transplant managed with conventional treatment is associated with substantial HCRU and costs. The burden remains particularly high for patients requiring multiple treatment courses for post-transplant CMV or for transplant recipients who develop myelosuppression or nephrotoxicity.